Cross continental increase in methane ebullition under climate change. Issue 1 (December 2017) - Aben, Ralf; Barros, Nathan; van Donk, Ellen; Frenken, Thijs; Hilt, Sabine; Kazanjian, Garabet; Lamers, Leon; Peeters, Edwin; Roelofs, Jan; Senerpont Domis, Lisette; Stephan, Susanne; Velthuis, Mandy; et al.
Abstract Methane (CH4 ) strongly contributes to observed global warming. As natural CH4 emissions mainly originate from wet ecosystems, it is important to unravel how climate change may affect these emissions. This is especially true for ebullition (bubble flux from sediments), a pathway that has long been underestimated but generally dominates emissions. Here we show a remarkably strong relationship between CH4 ebullition and temperature across a wide range of freshwater ecosystems on different continents using multi-seasonal CH4 ebullition data from the literature. As these temperature–ebullition relationships may have been affected by seasonal variation in organic matter availability, we also conducted a controlled year-round mesocosm experiment. Here 4 °C warming led to 51% higher total annual CH4 ebullition, while diffusion was not affected. Our combined findings suggest that global warming will strongly enhance freshwater CH4 emissions through a disproportional increase in ebullition (6–20% per 1 °C increase), contributing to global warming. The impacts of climate change on natural methane (CH4 ) emissions via ebullition are unclear. Here, using published and experimental multi-seasonal CH4 ebullition data, the authors find a strong relationship between CH4 ebullition and temperature across a wide range of freshwater ecosystems globally.